Mangrove Species Composition in The Mangrove Forest of Cendi Manik Village, Sekotong, West Lombok Regency - Martha, Eriko Thopan; Candri, Dining Aidil; Ahyadi, Hilman; Ghazali, Mursal; Munawaroh, Anggi Nurhardiyanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The mangrove forest in Cendi Manik Village, West Lombok Regency, consists of both natural and rehabilitated areas, the latter of which has been developed into the Bagek Kembar Mangrove Ecotourism site. While the growth of ecotourism has increased public and governmental attention toward the rehabilitated zone, concern for the natural mangrove forest has declined. This study aims to identify mangrove species composition and analyze vegetation density and diversity in the Cendi Manik mangrove area. The research was conducted from February to March 2024 using vegetation analysis methods across 15 plots distributed along three transects. The results identified six main mangrove species: Avicennia marina, A. alba, Rhizophora apiculata, R. mucronata, R. stylosa, and Sonneratia alba, with Rhizophora mucronata being the most dominant species, having the highest tree density of 440 individuals/ha. The total tree density reached 1,373.34 individuals/ha, which is categorized as dense according to Indonesian Ministry of Environment Regulation No. 201/2004. The species diversity index (H’) ranged from 1.54 to 1.61, indicating moderate to high diversity levels. The dominance of muddy substrates in the area supports the optimal growth of Rhizophora species. These findings highlight the ecological importance of conserving the remaining natural mangrove forests in Cendi Manik Village, given their vital role in coastal protection, carbon storage, and habitat provision for coastal biota. This research serves as a foundation for more comprehensive and sustainable conservation strategies in the region.